2009
DOI: 10.1681/asn.2008060559
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Deficiency Attenuates Renal Injury in Experimental Glomerulonephritis

Abstract: The P2X 7 receptor is a ligand-gated cation channel that is normally expressed by a variety of immune cells, including macrophages and lymphocytes. Because it leads to membrane blebbing, release of IL-1␤, and cell death by apoptosis or necrosis, it is a potential therapeutic target for a variety of inflammatory diseases. Although the P2X 7 receptor is usually not detectable in normal renal tissue, we previously reported increased expression of both mRNA and protein in mesangial cells and macrophages infiltrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 29 publications
6
90
0
Order By: Relevance
“…The function of P2X7 in collecting duct remains poorly understood. A previous study reported no abnormalities in renal morphology or histology in a different P2X7 KO mouse model (6-to 8-week-old female mice) [51]. In the present Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The function of P2X7 in collecting duct remains poorly understood. A previous study reported no abnormalities in renal morphology or histology in a different P2X7 KO mouse model (6-to 8-week-old female mice) [51]. In the present Fig.…”
Section: Discussionsupporting
confidence: 56%
“…This mouse model has been studied extensively; however, most studies have focused on the phenotype of younger animals. It has previously been reported that the Pfizer KO mouse displays no gross phenotypic differences at early ages [19,33,51]. In the present study, we allowed these mice to age, which revealed an unexpected increase in body mass due to greater lipid accumulation in older male KO mice.…”
Section: Discussionmentioning
confidence: 74%
“…P2X 7 mRNA expression levels were determined by real-time RT-PCR, by using a commercial kit (Rn00570451_m1; Applied Biosystems, Foster City, CA, USA), and normalized for the expression of GAPDH mRNA (4352338E; Applied Biosystems). These measurements were expressed as log 10 [2 35-CT1 /2 25-CT2 ], where 2 35-CT1 and 2 correspond to the expression levels of P2X 7 and GAPDH mRNA, respectively.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…2,3,25 Indeed, P2X 7 has recently been reported to be involved in various inflammatory processes of different pathological conditions, such as cerebral infarction 26 or ischemia, 27,28 lung inflammation and emphysema, 29 allergic airway inflammation, 30 unilateral urethral obstructive nephropathy 9 and accelerated nephrotoxic nephritis. 10 Several recent studies have provided convincing evidence that the renal proinflammmatory response has an important role in mediating salt-sensitive hypertension. 31,32 In a previous study, quantitative trait locus analysis identified the P2X 7 gene as a candidate gene for hypertension, by using F2 rats derived from DS and LEW rats.…”
Section: P2x 7 Expression Is Higher In the Kidneys Of Ds Ratsmentioning
confidence: 99%
See 1 more Smart Citation